The Relationship of Arcus Pedis Form with Running Speed in Markentho's Football Running Community at Manahan Stadium - Anggriani, Atika Febri; Utomo, Prasetyo Catur; Fauziah, Ika Fitri (Journal of Prosthetics Orthotics and Science Technology, 2024)
Background: Running speed refers to a person's ability to perform consecutive movements to cover a distance in the shortest possible time. This speed is influenced by the arch of the foot (arcus pedis), which can be classified as low, high, or average, and functions as a shock absorber when the foot contacts the ground. Common deformities in abnormal foot structures include pes cavus and flat feet. Aim: To determine the relationship between the condition of the arcus pedis and running speed in the Anak Buah Markentho running community at Manahan Stadium. Methods: This research was conducted on 25 members of a running community. The normality test was performed using the Shapiro-Wilk test, and the hypothesis was tested using Spearman's correlation. Results: The analysis yielded a significance value of 0.000 (p < 0.05), indicating a significant correlation between the shape of the arcus pedis and running speed. The Spearman correlation coefficient was 0.691, showing a positive and strong correlation. Conclusion: Greater deviations in the arch shape are associated with lower running speed, demonstrating a significant and strong correlation. This suggests a clear relationship between the shape of the arcus pedis and running speed.